2015
DOI: 10.1155/2015/174616
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Antifatigue Activities ofCordyceps militarisFruit Body Extract in Mouse Model

Abstract: Cordyceps militaris has been used extensively as a crude drug and a folk tonic food in East Asia due to its various pharmacological activities. Our study aims to investigate the effect of Cordyceps militaris fruit body extract (CM) on antifatigue in mouse model. Two week CM administration significantly delayed fatigue phenomenon which is confirmed via rotating rod test, forced swimming test and forced running test. Compared to nontreated mouse, CM administration increased ATP levels and antioxidative enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…These results were in accordance with previous reports about antifatigue activities of Cordyceps fungi. 1, [24][25][26] Our results also showed that SBCC increased the strength of skeletal muscle. The effects of SBCC might be related to promotion of myoblast differentiation, protein synthesis and cell metabolism through activation of the AKT, mTOR and AMPK signaling pathways.…”
Section: Discussionsupporting
confidence: 75%
“…These results were in accordance with previous reports about antifatigue activities of Cordyceps fungi. 1, [24][25][26] Our results also showed that SBCC increased the strength of skeletal muscle. The effects of SBCC might be related to promotion of myoblast differentiation, protein synthesis and cell metabolism through activation of the AKT, mTOR and AMPK signaling pathways.…”
Section: Discussionsupporting
confidence: 75%
“…High consumption of energy during intense and repetitive exercise accelerates the occurrence of free radicals such as reactive oxygen species. There is increasing evidence that the accelerated accumulation of reactive oxygen species leading to oxidative stress contributes strongly to muscle fatigue during exercise (Song et al, ). SOD is regarded as one of the defense lines of the antioxidant enzyme system, able to scavenge free radicals owing to exhausting physical exercise and relieve physical stress and fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen can be transformed into oxygen free radicals (OFR), which serve important roles in signal transduction and other physiological processes (14). Unremitting and strenuous exercise increases energy consumption and accelerates the accumulation of OFR derivatives, such as ROS, leading to oxidative stress and muscle fatigue.…”
Section: Tm (G/kg) Tm (G/kg) ----------------------------------------mentioning
confidence: 99%
“…Various species of fungi and certain herbs may postpone the onset of fatigue, improve athletic ability and enhance the elimination of fatigue-related metabolites (13). The anti-fatigue effects of Tricholoma matsutake, Cordyceps militaris and Antrodia cinnamomea in murine models have been examined in previous studies by assessing their effect on oxidative stress (3,14,15). Tuber melanosporum (TM), a fungus containing unique bioactive metabolites, contains important nutrients including proteins, unsaturated fatty acids, amino acids, sphingolipids, cerebrosides and polysaccharides (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation